2022
DOI: 10.1002/rmv.2379
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID 19 on the outcomes of thrombectomy in stroke patients: A systematic review and meta‐analysis

Abstract: We aimed to conduct the current meta‐analysis to provide better insight into the efficacy of mechanical thrombectomy (MT) in managing COVID‐19 patients suffering from a stroke. An electronic search was conducted through eight databases for collecting the current evidence about the efficacy of MT in stroke patients with COVID‐19 until 18 December 2021. The results were reported as the pooled prevalence rates and the odds ratios (ORs), with their corresponding 95% confidence intervals (CI). Out of 648 records, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
(141 reference statements)
3
2
0
Order By: Relevance
“…Our laboratory analysis was in accordance with these studies. When analyzing the outcome of mechanical thrombectomy procedures, our report showed similar results to some studies regarding a favorable recanalization mTICI score (>2B), which was comparable in COVID-19 and non-COVID-19 groups, as reported earlier [ 11 , 36 , 37 ]. Studies, including ours, did not find a correlation between procedure-related complications such as sICH or SAH [ 11 , 12 , 36 , 37 ], and occurrence of ICH was comparable with large studies [ 38 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our laboratory analysis was in accordance with these studies. When analyzing the outcome of mechanical thrombectomy procedures, our report showed similar results to some studies regarding a favorable recanalization mTICI score (>2B), which was comparable in COVID-19 and non-COVID-19 groups, as reported earlier [ 11 , 36 , 37 ]. Studies, including ours, did not find a correlation between procedure-related complications such as sICH or SAH [ 11 , 12 , 36 , 37 ], and occurrence of ICH was comparable with large studies [ 38 ].…”
Section: Discussionsupporting
confidence: 89%
“…When analyzing the outcome of mechanical thrombectomy procedures, our report showed similar results to some studies regarding a favorable recanalization mTICI score (>2B), which was comparable in COVID-19 and non-COVID-19 groups, as reported earlier [ 11 , 36 , 37 ]. Studies, including ours, did not find a correlation between procedure-related complications such as sICH or SAH [ 11 , 12 , 36 , 37 ], and occurrence of ICH was comparable with large studies [ 38 ]. The modified Rankin Scale score, as a rank of functional independence after AIS, showed no difference between our groups, as previously reported [ 37 ], although some studies reported higher mortality rate in COVID-19 patients [ 25 , 36 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Comparing TICI ≥2b scores between COVID-19 and non-COVID-19 stroke patients treated with MT, they found no significant difference. However, mortality after MT surgery was substantially higher in COVID-19 stroke patients compared to non-COVID-19 stroke patients ( 84 ). The recanalization status, NIHSS score at 24 h after MT, and sICH were predictors of mortality after MT in patients with AIS ( 81 ).…”
Section: Acute Stroke Treatment During the Covid-19 Pandemicmentioning
confidence: 99%
“…This approach can be remarkably useful in the evaluation process since some details cannot be obtained by rigid or flexible endoscopic approaches. Stroboscopy-based surveillance might also be useful in evaluating patients suffering from related malignancies (21,22).…”
Section: Evaluation and Differential Diagnosismentioning
confidence: 99%